Ultrabroadband Wavelength Conversion with Tellurite Waveguides - Fagotto, Eric A. M.; Bonani, Luiz H.; Abbade, Marcelo L. F.; Marconi, Jorge D.; Miranda, Uriel R. C.; Aldaya, Ivan; Rossi, Sandro M.; Galdino, Lidia; Martins, Indayara B. (Institute of Electrical and Electronics Engineers (IEEE), 2021)
In this work, we propose and investigate numerically a two-stage one-pump four-wave mixing (FWM) device for guard-band-less wavelength conversion. This device can convert all signals within the C-band to the L-band and, afterwards, return them to the C-band. The nonlinear medium for FWM is a spiral-shaped tellurite waveguide with a footprint of 2.5 mm2. Our simulation results indicate, after wavelength conversion (C- to L-band and back to C-band at the destination) 80×56-Gb/s quadrature phase shift keying signals could be propagated in networks with diameters as large as 640 km.
Keywords: Four-wave mixing; Guard-band-less conversion; Tellurite; Wavelength conversion